Short- and long-term efficacy of intra-articular injections with betamethasone as part of a treat-to-target strategy in early rheumatoid arthritis: impact of joint area, repeated injections, MRI findings, anti-CCP, IgM-RF and CRP. Issue 6 (1st February 2012) - Hetland, Merete Lund; Østergaard, Mikkel; Ejbjerg, Bo; Jacobsen, Søren; Stengaard-Pedersen, Kristian; Junker, Peter; Lottenburger, Tine; Hansen, Ib; Andersen, Lis Smedegaard; Tarp, Ulrik; Svendsen, Anders; Pedersen, Jens Kristian; et al.
Abstract : Objective: To investigate the short-term and long-term efficacy of intra-articular betamethasone injections, and the impact of joint area, repeated injections, MRI pathology, anticyclic citrullinated peptide (CCP) and immunoglobulin M rheumatoid factor (IgM-RF) status in patients with early rheumatoid arthritis (RA). Methods: During 2 years of follow-up in the CIMESTRA trial, 160 patients received intra-articular betamethasone in up to four swollen joints/visit in combination with disease-modifying antirheumatic drugs. Short-term efficacy was assessed by EULAR good response. Long-term efficacy by Kaplan–Meier plots of the joint injection survival (ie, the time between injection and renewed flare). Potential predictors of joint injection survival were tested. Results: 1373 Unique joints (ankles, elbows, knees, metacarpophalangeal (MCP), metatarsophalangeal, proximal interphalangeal (PIP), shoulders, wrists) were injected during 2 years. 531 Joints received a second injection, and 262 a third. At baseline, the median numbers of injections (dose of betamethasone) was 4 (28 mg), declining to 0 (0 mg) at subsequent visits. At weeks 2, 4 and 6, 50.0%, 58.1% and 61.7% had achieved a EULAR good response. After 1 and 2 years, respectively, 62.3% (95% CI 58.1% to 66.9%) and 55.5% (51.1% to 60.3%) of the joints injected at baseline had not relapsed. All joint areas had good 2-year joint injection survival, longest for the PIP joints: 73.7% (79.4% to 95.3%). 2-Year joint injection survival was higher for first injections: 56.6% (53.7% to 59.8%) than for the second: 43.4% (38.4% to 49.0%) and the third: 31.3% (25.0% to 39.3%). Adverse events were mild and transient. A high MRI synovitis score of MCP joints and anti-CCP-negativity were associated with poorer joint injection survival, whereas IgM-RF and C-reactive protein were not. Conclusion: In early RA, intra-articular injections of betamethasone in small and large peripheral joints resulted in rapid, effective and longlasting inflammatory control. The cumulative dose of betamethasone was low, and the injections were well tolerated.